Simulation-based training platforms for arthroscopy: A randomized comparison of virtual reality learning to benchtop learning. - Middleton, R; Alvand, A; Garfjeld Roberts, P; Hargrove, C; Kirby, G; Rees, J (Elsevier, 2017)
Purpose To determine whether a virtual reality (VR) arthroscopy simulator or benchtop (BT) arthroscopy simulator showed superiority as a training tool. Methods Arthroscopic novices were randomized to a training program on a BT or a VR knee arthroscopy simulator. The VR simulator provided user performance feedback. Individuals performed a diagnostic arthroscopy on both simulators before and after the training program. Performance was assessed using wireless objective motion analysis and a global rating scale. Results The groups (8 in the VR group, 9 in the BT group) were well matched at baseline across all parameters (P > .05). Training on each simulator resulted in significant performance improvements across all parameters (P < .05). BT training conferred a significant improvement in all parameters when trainees were reassessed on the VR simulator (P < .05). In contrast, VR training did not confer improvement in performance when trainees were reassessed on the BT simulator (P > .05). BT-trained subjects outperformed VR-trained subjects in all parameters during final assessments on the BT simulator (P < .05). There was no difference in objective performance between VR-trained and BT-trained subjects on final VR simulator wireless objective motion analysis assessment (P > .05). Conclusions Both simulators delivered improvements in arthroscopic skills. BT training led to skills that readily transferred to the VR simulator. Skills acquired after VR training did not transfer as readily to the BT simulator. Despite trainees receiving automated metric feedback from the VR simulator, the results suggest a greater gain in psychomotor skills for BT training. Further work is required to determine if this finding persists in the operating room. Clinical Relevance This study suggests that there are differences in skills acquired on different simulators and skills learnt on some simulators may be more transferable. Further work in identifying user feedback metrics that enhance learning is also required.